The Application of Artificial Intelligence in Mitigation of Financial Investment Risk and The Future Challenges Faced: A Systematic Literature Review - Surya Dewi, Ni Made Sintya; Ida Ayu Nirma Prameswari; Bagiana, I Kadek (Islamic Accounting Journal, 2025)
Objectives & Objects: This article aims to explain the role of applying artificial intelligence in mitigating financial investment risks and future challenges faced by the existence of this AI use. Methods: This study adopts a Systematic Literature Review approach. Results & Conclusions: The findings of this study confirm that the role of applying AI as an innovation to reduce financial risk is that artificial intelligence can increase operational efficiency by processing and analyzing data quickly, saving time and human resources. AI can also help make better decisions in financial risk management. This can optimize financial performance and reduce losses. Limitations: The weakness of this study is the limited reference sources to be able to review this topic in more depth because this topic is still relatively new. Implications: By implementing AI, financial institutions can identify risks more accurately and faster. The application of AI does provide many benefits in the financial sector because it can be used as a tool to mitigate financial risks faced by companies, but the benefits of utilizing AI are inseparable from future challenges that may be faced. The challenges faced include the need for adequate regulation, proper data protection, cybersecurity risks, and gaps in technological skills among financial professionals.